Internalization of Pancasila Student Profile Values in Mataram State High School: An Islamic Perspective on Education and Ethics - Hully Hully; Evana Gina Shantika; Maftuh Ihsan Nanda Kurniawan (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
This research aims to study and analyze the internalization of Pancasila student profile values from the perspective of Islamic education and character in high school. The research method used is qualitative research with data collection techniques using observation, interviews, and documentation. Data was analyzed by employing the Miles and Huberman model, starting with data collection, condensation, and display and concluding. Diligent observation, extended participation, references, and triangulation ensure the validity of the data. The formulation of the problem in this research is how to internalize the values ​​of the Pancasila student profile in Islamic religious education and character in high school. The results of this research can conclude that the internalization of Pancasila student profile values in perspective Islamic education and character at school was carried out by planning as an initial step, such as preparing learning tools in the form of teaching modules with independent implementation. Curriculum starting in 2021 and second, implementing learning as a core activity in internalizing the values ​​of the Pancasila student profile in learning Islamic religious education and character at school, which includes values such as the value of faith and devotion to God Almighty, as well as having noble morals, the value of cooperation, critical reasoning, creative values, and the value of Independence. Third, evaluation of the internalization of Pancasila student profile values in perspective Islamic education and character at school includes evaluating attitudes, knowledge, and skills through oral, written, portfolio, and self-assessment tests for students at school.